Reconstructing Past Rates of Atmospheric Dust Deposition in the Athabasca Bituminous Sands Region Using Peat Cores from Bogs. (6th October 2017) - Mullan‐Boudreau, Gillian; Davies, Lauren; Devito, Kevin; Froese, Duane; Noernberg, Tommy; Pelletier, Rick; Shotyk, William
Abstract: Open‐pit mining of the Athabasca Bituminous Sands generates considerable quantities of mineral dusts, but there is no published record of the amount of material deposited in the surrounding environment via the atmosphere since the industry began in 1967. Contemporary and past rates of atmospheric dust deposition were reconstructed using age‐dated peat cores ( 210 Pb and 14 C) collected from five bogs in the vicinity of mines and upgraders and from two bogs far removed from industrial activities. The main objective of this study was to quantify the impact of industry on dust emissions, and to do this, the variation in natural "background" rates of mineral matter accumulation also had to be determined. A second objective was to characterize the size, mineralogical composition, and morphology of the particulate matter emitted to better understand potential environmental consequences of dust emissions. The concentrations of acid insoluble ash and Th (a surrogate for insoluble mineral matter) were determined to calculate dust accumulation rates. Scanning electron microscopy with energy‐dispersive X‐ray analysis failed to reveal much variation in mineralogical composition, but near industry, the size of the particles was more variable. The abundance of fly ash particles increased with depth, which suggests that emissions from upgrader stacks may have declined over time. A comparison of acid‐insoluble ash inventories with the pH of the porewaters suggests that the acid‐soluble ash fraction of the dusts deposited may have impacted the chemical composition of the bog waters. Copyright © 2017 John Wiley & Sons, Ltd.